Thermal performance of fly ash geopolymeric mortars containing phase change materials - Kheradmand, Mohammad (2018)
This paper reports experimental results on the thermal performance of fly ash-based  geopolymeric mortars containing different percentages of phase change materials  (PCMs). These materials have a twofold eco-efficient positive impact. On one hand,  the geopolymeric mortar is based on industrial waste material. And on the other  hand, the mortars with PCM have the capacity to enhance the thermal performance  of the buildings. Several geopolymeric mortars with different PCM percentages  (10%, 20%, 30%) were studied for thermal conductivity and thermal energy storage